A Case of Neonatal Coxsackie B2 Meningo-Encephalitis in which Serial Magnetic Resonance Imaging Findings Reveal the Development of Lesions - Hirata, O.; Ishikawa, N.; Mizoguchi, Y.; Nakamura, K.; Kobayashi, M. (Neuropediatrics, 2011)
We report a patient with neonatal Coxsackie B2 meningo-encephalitis in whom magnetic resonance imaging (MRI) could be performed serially from the early stage of the disease. The patient was a 12-day-old girl born at a gestational age of 37 weeks. She was hospitalized due to poor suckling. During her hospital stay, she developed clonic seizures in the right upper and lower limbs. Coxsackie B2 virus was detected, and a diagnosis of viral encephalitis was made. The first diffusion-weighted images (DWI) showed an abnormal high-intensity area restricted to the corpus callosum and posterior limb of the internal capsule 8 h after onset of seizures. Repeated MRI revealed damage to the white matter, which finally changed into diffuse excessive necrosis followed by cystic leukomalacia. Early DWI is valuable for the early detection and diagnosis of neonatal meningo-encephalitis. This is the first report of the detailed neuroradiological course of neonatal Coxsackie B2 meningo-encephalitis.
Keywords: neonates; Coxsackie B2; meningo-encephalitis; magnetic resonance imaging; diffusion-weighted imaging